Blood Pressure Management in Acute Ischemic Stroke - Jayesthiwi Wanami Putri, Ni Made Wini (Jurnal Health Sains, 2025)
Stroke is a leading cause of death worldwide, with acute ischemic stroke (AIS) being one of its most common forms. AIS occurs when the blood supply to the brain is blocked due to thrombosis or embolism, leading to ischemic brain tissue. Blood pressure management in AIS patients is crucial, as it directly impacts patient outcomes, such as preventing further brain damage, recurrent stroke, and other cerebrovascular complications. The 2019 AHA/ASA guidelines provide distinct strategies for blood pressure management, depending on whether the patient is undergoing reperfusion therapy. For patients with AIS without reperfusion therapy, blood pressure should not be aggressively lowered unless it exceeds 220/120 mmHg. In contrast, for patients undergoing reperfusion therapy, such as IV-tPA or endovascular therapy, blood pressure should be maintained below 185/110 mmHg before and during the procedure. Different antihypertensive agents are used, with short-acting drugs such as labetalol, nicardipine, and hydralazine being commonly employed. Managing blood pressure correctly during AIS treatment is critical in preventing complications such as hemorrhagic transformation and ensuring better long-term neurological outcomes.